High seroprevalence to SARS-CoV-2 among healthcare and non-healthcare workers of the ophthalmology center - N. V. Palyanova; M. G. Chechenin; A. N. Trunov; I. A. Sobolev; A. M. Shestopalov (Acta Biomedica Scientifica, 2024)
Background. The pandemic of COVID-19 raised safety concerns for healthcare workers while non-medical personnel were left unattended. Comparing the levels of seroprevalence to SARS-CoV-2 and vaccination in different employee groups will allows us to assess the risk of infection and develop a strategy to minimize the spread of infections in medical institutions in future.The aim. To identify the level of seroprevalence to SARS-CoV-2 for seven groups of medical center workers. Methods. The seroprevalence to SARS-CoV-2 was analyzed in 361 employees of the ophthalmology center in mid-2021. Data on the level of specific IgM and IgG antibodies were compared with questionnaire, including occupation data.Results. Depending on occupation, workers were divided into seven groups. The average seroprevalence rate for all employees was 82.3 %, and the percentage of vaccinated employees was 27.4 %. The lowest level of seroprevalence was found in the group of maintenance staff (55.0 %) which is significantly lower (p ˂ 0.05) than in the groups of doctors (84.4 %), nurses (85.6 %), administrative stuff (82.6 %) and cafeteria stuff (77.7 %). The seroprevalence rate for cleaning staff was 84.6 % and for pharmacy workers it was 80 %. The highest vaccination coverage was among doctors – 50.0 %, the lowest was among cafeteria and kitchen staff – 7.4 %.Discussion. We believe the high seroprevalence is associated with asymptomatic spread of SARS-CoV-2.Conclusions. High seroprevalence was among doctors and nurses, pharmacy workers, canteen workers, cleaners, as well as administration workers. Anti-epidemic measures for these groups will reduce the spread of  infectious diseases and help retain staff during the seasonal increase in incidence.